위장조영검사에서 피폭선량 저감 - 임병학; Byung-hak Lim; 천권수; Kwon Su Chon (Journal of the Korean Society of Radiology, 2017)
위장조영검사는 위내시경검사에 비해 비침습적이고, 일시적인 변비나 복통 외에 특별한 부작용이 없어 위내시경 검사가 어려운 환자나 노약자에게 유용하며, 위의 전체 모습을 볼 수 있어 병변의 위치를 정확히 묘사할 수 있는 장점으로 현재 상부위장관 질환의 진단에 많이 이용되고 있다. 하지만 수검자의 위장조영검사에 대한 전반적인 이해 부족으로 인하여 발생되는 검사 중 부적절한 움직임과 호흡조절로 피폭선량이 증가할 가능성이 있다. 위장조영검사 수검자의 검사에 대한 이해를 도와 검사 중 적절한 협조를 유도하고, 재촬영 건수의 감소와 검사 시간의 단축, 수검자의 피폭선량을 감소시키기 위한 방법으로 위장조영검사의 검사 과정과 주의사항을 동영상으로 제작하여 검사 전 대기시간을 이용하여 시청하게 함으로써, 동영상을 이용한 사전교육이 검사시간 단축과 재촬영 건수, 피폭선량 감소에 어느 정도 효과가 있는지 조사하였다. 30대부터 80대까지 각각 20명씩 선출한 120명을 대상으로 교육 전·후의 피폭선량과 검사 시간, 재촬영 건수를 평가하였다. 그 결과 전 연령대 평균으로 나타낸 교육 전 수검자의 피폭선량은 3171.83 μGy·m², 교육후 수검자의 피폭선량은 2931.73 μGy·m²로 나타났고, 검사시간은 교육 전 8.05 min, 교육 후 6.75 min으로 나타났으며, 재촬영 건수는 교육 전 1.68건, 교육 후 1.22건으로 나타났다. 따라서 동영상 교육을 이용하여 위장조영검사 수검자를 대상으로 시행한 위장조영검사에 대한 사전 정보제공이 위장조영검사 수검자의 검사시간 단축, 재촬영 건수와 피폭선량의 감소에 영향을 미쳤다는 것을 확인할 수 있었다. Upper gastrointestinal series is non-invasive examination, and it is useful for patients or elderly patients who have difficulty in endoscopic examination because of absence of any side effects other than temporary constipation or abdominal pain. The entire image of the gastrointestinal tract can be seen and have been widely used in the diagnosis of upper gastrointestinal diseases. However, there is a possibility that radiation dose increases due to improper movement and breath control, when examination is carried out by lack of understanding the overall inspection process for the upper gastrointestinal series. In upper gastrointestinal series to increase understanding of examination, to induce appropriate cooperation during examination, to reduce the number of retakes and shorten examination time, and to reduce dose of the subject, the procedure and precautions of the gastrointestinal test were made as a movie. We investigated the effectiveness of pre-education using the movie to reduce the inspection time, the number of re-shoots, and the reduction of exposure dose by watching the movie during the waiting time before examination. 120 patients that were selected each 20 patients aged from 30s to 80s were evaluated were evaluated for exposure dose, examination time, and the number of retakes before and after the movie training. The radiation dose, the examination time, and the number of retakes were respectively 3171.83 μGy·m2 and 2931.73 μGy·m2, 8.05 min, and 6.75 min, and 1.68 times and 1.22 times before and after movie training. It can be concluded that the movie training on the gastrointestinal examination influences the reduction of the examination time, the number of retakes and the reduction of the radiation dose.